The Teacher's Creativities in the Implementation of Group Work in EFL Classroom - Ari Gusti Sundari; Muhammad Dalimunthe; Didik Santoso (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the forms of teacher creativity demonstrated in the implementation of group work in an EFL classroom. Creativity in instructional practice is essential for supporting student engagement, especially in vocational education where practical communication skills are prioritized. The study aims to investigate an EFL teacher employs creative strategies when organizing, facilitating, and responding to group work dynamics. Data were collected through classroom observations, semi structure interviews, and documentation, and analyzed using Miles and Huberman’s (2014) interactive model of data condensation, data display, and conclusion drawing. The findings reveal three major forms of teacher creativity: Product Creativity, Process Creativity, and Reactive Creativity. Product Creativity was reflected in the teacher’s use of digital learning materials, gamified tasks, authentic resources, and visually enriched media to support group activities. Process Creativity emerged through varied grouping arrangements, systematic role assignment, creative monitoring techniques, and strategic language management to guide students’ interaction. Reactive Creativity appeared when the teacher adapted spontaneously to classroom situations such as mixed proficiency levels, behavioral challenges, and technical disruptions. Overall, the findings underscore that teacher creativity in group work extends beyond creating innovative materials; it also involves adaptive facilitation, responsive decision-making, and context-sensitive problem-solving. These insights contribute to a deeper understanding of how creativity shapes group work practices in EFL vocational settings and offer practical recommendations for promoting more engaging and effective collaborative learning in similar contexts.